A Perspective on the Implementation of Management Science - Anderson, John; Hoffmann, Thomas (Academy of Management Review, 1978)
Three different dimensions of OR/MS efforts exist. Experience has shown undue emphasis on one of these—installation—at the expense of the other two—implementation and integration. Definition and understanding of these dimensions within the conceptual framework presented will allow better planning, and conduct and evaluation of OR/MS efforts.